The odyssey of Savita and Krishna (A) - Rajadhyaksha, Ujvala; Vohra, Neharika; Moorthy, Ravi (London : SAGE Publications Ltd, 2017)
This case is in four parts, highlighting the crossroads at which the protagonist Savita finds herself in and the difficulties she faces in balancing her career aspirations with family responsibilities. A Fellow of Indian Institute of Management (IIM) Ahmedabad, Savitas dilemmas concern working in a prestigious management institute in Kolkata versus getting a job in Mumbai in order to psychologically and financially support her family and get married; joining her husband in China on his posting versus going to the US on a prestigious fellowship prioritizing her career, and finally, starting a family versus postponing the decision till the couple were together and reasonably settled in their respective careers.
Originally published: Rajadhyaksha, U., Vohra, N., & Moorthy, R. (2013). The odyssey of Savita and Krishna (A). OB0213. Ahmedabad: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Indian Institute of Management, Ahmedabad; Work-life balance -- India -- Case studies; International business enterprises -- Management -- Case studies; Management -- India -- Case studies